Thermo-ecological performance analysis of a Joule-Brayton cycle (JBC) turbine with considerations of heat transfer losses and temperature dependent specific heats - Gonca, Guven; Sahin, Bahri (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
This study presents a new performance analysis criterion called Effective Ecological Power Density (EFECPOD) and its application to a Joule-Brayton cycle (JBC) turbine. Effective efficiency (EE), effective power (EP), cycle temperature ratio and turbine volume are considered together and the performance is stated a unique value by the developed criterion. emissions formation and turbine dimensions are considered by the cycle temperature ratio and turbine volume, respectively. The turbine volume is also related to production cost of the heat engine. Therefore, the proposed criterion is essential for multipurpose optimization. Furthermore, this criterion can be developed and applied to the other gas cycles and heat engines. Also, a performance investigation for the JBC gas turbine in terms of EE, EP and effective power density (EPD) has been carried out using a new finite-time thermodynamics modeling (FITM). The influences of engine design parameters such as cycle temperature ratio, cycle pressure ratio, turbine speed, intake temperature, intake pressure and equivalence ratio on the EE, EP, EPD and EFECPOD have been examined. The results presented can be an essential tool for JBC turbine designers. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Joule-Brayton cycle; Gas turbine performance; Power density; Finite-time thermodynamics; INJECTED DIESEL-ENGINE; GAS-TURBINE; MILLER CYCLE; STEAM INJECTION; THERMOECONOMIC ANALYSIS; REGENERATIVE BRAYTON; THERMODYNAMIC CYCLES; POWER-PLANTS; NATURAL-GAS; OPTIMIZATION; Thermodynamics; Energy & Fuels; Mechanics